Security, Religion, and Political Culture: A Defense of Weak Disestablishment - Prud'homme, Joseph (Religions, 2019)
Many, especially in the West, have long argued against state religious establishments on the ethical grounds of the rights of freedom of conscience and personal autonomy. Situating the question of religious establishment within the field of Religion and Security-an important and growing aspect of the Religious Studies discipline-allows for new interpretive possibilities. This paper explores the impact of religious disestablishment on the state's task of provisioning security from violent religious extremism. Could it be that states which have disestablished a formal or deeply embedded informal tie with religion are less able to provide security to their citizenry? I examine this question and develop the contention that religious disestablishment in the West has actually harmed the state's capacity to deal effectively with violent religious extremism. In turn, this finding requires us to reconsider the normative bases of strict church/state separation and provides one element within a range of arguments for what I label 'weak disestablishment.'